Could exit rules be self-enforcing in the EU? The cases of France and Germany - Robert Kappius; Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2015)
[Introduction] Exit rules allow for a temporary or permanent withdrawal from international cooperative regimes. For the ongoing crisis in the European Monetary Union (EMU), such rules are seen as a desirable solution to enhance flexibility in case of economic and political shocks in member countries and to restrict fiscal externalities in the Euro zone. As the EU acts as a union of sovereign countries, politically powerful nations like France or Germany are likely to blockade or circumvent such a rule, if it negatively affects their interest. The underlying strategic problem of self-enforceability is largely neglected with respect to an EU exit rule. This contribution to the political economy of exit and escape rules aims at assessing conditions of voluntary adherence to an exit scheme by all parties of a common currency union such as the EMU. [...]
Keywords: 330